IMAGE ENHANCEMENT MENGGGUNAKAN METODE LINEAR FILTERING DAN STATIONARY WAVELET TRANSFORM - Tena, Silvester (Majalah Ilmiah Teknologi Elektro, 2012)
The aim of the research is image enhancement using the linear filtering and the Stationary Wavelet Transform (SWT) method. The linear filtering method using in this research is median filter, low pass filter and wiener filter and the SWT method using wavelet haar/db1. The Noise as input for source image is salt&pepper and gaussian. The quality of image enhancement determined by qualitative and quantitative assesments. Quantitative performance of the method can be measured by MSE and PSNR. The research shows that ever greater of  the noise density cause the value of MSE uphill progressively but the value of PSNR decrease progressively. The qualitative assessment depend on the everyone perception to the image enhancement. The result obtained shows that the SWT method better than linear filtering method.